Expressive Means in Tatar Translation of Alexander Sergeevich Pushkin’s Novel "Eugene Onegin" - Fakhrieva, Leilya Khambalevna; Kirillova, Zoya Nikolaevna; Sahin, Liaisan (Journal of History Culture and Art Research, 2017)
The comparative study of the Tatar translation of the novel in verses "Eugene Onegin" by Alexander Sergeevich Pushkin and the original is performed in this scientific article in order to determine its artistic quality in the aspect of the lexical expressive means transfer of the original. The following methods and techniques were used in the work: comparative and hermeneutic method, etc. The study is based on the translation of Pushkin's novel, which was performed in the early 1950s, by Tatar poets Ahmet Iskhak, Ahmed Faizi and Shaykhi Mannur. In 1930s the novel was already magnificently translated by Fathi Burnash, but soon it was declared an "enemy of the people", and thus the regional committee of the party created a brigade of the best poets and ordered the translation to be published urgently. Based on the analysis of the novel in verse "Eugene Onegin" from the point of view of the lexical pictorial means of language use, we have discovered that Pushkin's language is full of rich imagery and a high degree of metaphorization and epithets. One of the most frequently used lexical stylistic devices in the novel in verse is metaphor and epithet. The author uses both simple and expanded metaphors. The latter can cover whole sentences or several sentences, forming the chain of metaphors for general semantics.